Quantitative Regulation of Interlayer Space of NH4V4O10 for Fast and Durable Zn2+ and NH4+ Storage. Issue 9 (25th January 2023) - Li, Shuyue; Yu, Dongxu; Liu, Jingyi; Chen, Nan; Shen, Zexiang; Chen, Gang; Yao, Shiyu; Du, Fei
Abstract: Layered vanadium‐based oxides are the promising cathode materials for aqueous zinc‐ion batteries (AZIBs). Herein, an in situ electrochemical strategy that can effectively regulate the interlayer distance of layered NH4 V4 O10 quantitatively is proposed and a close relationship between the optimal performances with interlayer space is revealed. Specifically, via increasing the cutoff voltage from 1.4, 1.6 to 1.8 V, the interlayer space of NH4 V4 O10 can be well‐controlled and enlarged to 10.21, 11.86, and 12.08 Å, respectively, much larger than the pristine one (9.5 Å). Among them, the cathode being charging to 1.6 V (NH4 V4 O10 ‐C1.6), demonstrates the best Zn 2+ storage performances including high capacity of 223 mA h g −1 at 10 A g −1 and long‐term stability with capacity retention of 97.5% over 1000 cycles. Such superior performances can be attributed to a good balance among active redox sites, charge transfer kinetics, and crystal structure stability, enabled by careful control of the interlayer space. Moreover, NH4 V4 O10 ‐C1.6 delivers NH4 + storage performances whose capacity reaches 296 mA h g −1 at 0.1 A g −1 and lifespan lasts over 3000 cycles at 5 A g −1 . This study provides new insights into understand the limitation of interlayer space for ion storage in aqueous media and guides exploration of high‐performance cathode materials. Abstract : Here, it is shown that via increasing the cutoff voltage from 1.4, 1.6, to 1.8 V, the interlayer space of NH4 V4 O10 can be well‐controlled and enlarged quantitatively to 10.21, 11.86, and 12.08 Å, respectively, much larger than the pristine one (9.5 Å), resulting in better zinc‐ion storage performance.